Hot water sanitization of a commercial mushroom disk slicer to inactivate Listeria monocytogenes. (March 2020) - Tobin, Hilary M.; Lele, Saurabh R.; Cutter, Catherine N.; Anantheswaran, Ramaswamy C.; LaBorde, Luke F.
Abstract: Industrial food slicing equipment that is difficult to clean and sanitize can become a reservoir of Listeria monocytogenes . Some commercial mushroom slicing operations have attempted to manage cross-contamination risks by periodically immersing detachable slicer heads in heated water maintained at varying temperatures for different times. In this study, the efficacy of hot water disinfection treatments to eliminate L. monocytogenes from commercial mushroom slicers was examined. Fourteen L. monocytogenes strains, including several obtained from mushrooms or mushroom processing environments, were screened for heat tolerance at 60 °C for 6 min. The 6 most heat tolerant strains were used to prepare a microbial cocktail for thermal inactivation studies. Heat tolerance of planktonic cells was not affected by incubation at 30 °C for up to 7 days, or the extent to which they adhered to stainless-steel coupons under the same conditions. Respective L. monocytogenes D50, D60, and D70 -values of 11.5 min, 1.90 min, and 1.0 min were not higher than D-values for a L. innocua isolate at the same temperatures. Heat penetration studies, conducted on the slicer head immersed in a heated clean-out-of-place (COP) wash tank, determined that the slowest-to-heat food contact location (cold spot) was the at the interface of one of the blade-spacers with the horizontal slicer drive shaft. A microbial challenge study was conducted by disassembling the slicer head, inoculating the cold spot with 7 log cells L. innocua surrogate, and subjecting the reassembled slicer head to water temperatures of 55 °C, 65 °C, or 75 °C for 93, 16.4, or 6.5 min. Complete elimination of L. innocua cells for each slicer head treatment demonstrated the feasibility of hot water sanitization treatments to minimize L. monocytogenes food safety risks. Highlights: Hot water treatment of mushroom slicers to eliminate Listeria monocytogenes was studied. Pre-incubation of planktonic or adhered cells did not increase heat-tolerance. Heat penetration studies were conducted to determine the slicer cold spot location. A pilot plant hot water challenge study was conducted using a L. innocua surrogate. Parameters for elimination of L. monocytogenes on mushroom slicers were confirmed.